Dissecting long-term Bund yields in the run-up to the ECB's Public Sector Purchase Programme - Wolfgang Lemke; Thomas Werner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Starting in summer 2014, markets began to build up expectations that the European Central Bank (ECB) would embark on large-scale sovereign bond purchases. The ECB's Public Sector Purchase Programme (PSPP) was eventually announced on 22 January 2015 and purchases started in March. Both during the run-up phase to the PSPP announcement day and for the day itself, German government bond yields declined significantly. Using an affine term structure model, we evidence that the yield declines are almost fully attributable to a decline in the term premium as opposed to the expectations component. This speaks in favour of the conjecture that the PSPP transmits to long-term yields mainly via a portfolio re-balancing channel rather than a (policy rate) signalling channel. The results prove robust against changing the number of factors in the model, the estimation sample and the estimation approach.
Keywords: E43; E52; 330; term structure of interest rates; large-scale asset purchases; term